Uncertain demurrage and detention decisions in hinterland container management - Jeong, Yoonjea; Kim, Gwang; Shin, Youngchul (International Transactions in Operational Research, 2025)
Due to the global supply chain crisis, the container supply chain has been characterized by heightened uncertainty, leading to periodic disruptions in the productivity of container flows. To adeptly navigate these challenges, this study provides individual free-time policy on hinterland container operation systems in the face of uncertainty. The investigation unfolds through the presentation of two analytical models, rooted in both demurrage- and detention-based models with practical implementation. Within these models, we explicitly formulate each optimization problem within a spectrum of scenarios encompassing the tardiness and earliness of container retrieval and return by a consignee. Through extensive numerical analyses, we elucidate the intricate trade-offs associated with decision variables of container supply chain members, offering a comprehensive understanding of their impact on the level of uncertainty. Employing a comparative approach, we validate the proposed models by providing valuable insights and guidelines pertaining to optimal demurrage and detention processes among uncertain conditions.
Keywords: Container management; Demurrage and detention charge; Global supply chain; Individual free-time policy; Inland container management; Maritime logistics; Periodic disruption; Retrieval and return process; Supply chain crisis; Uncertainty; demurrage and detention charges; individual free-time policy; inland container management; maritime logistics; retrieval and return processes; uncertainty